Aloe vera for Dry Mouth Denture Patients – Palliative Therapy - Abdul Habeeb Bin Mohsin; S Varalakshmi Reddy; M Praveen Kumar; Sarah Samee (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Xerostomia (dry mouth) is dryness of the mouth which is due to reduced salivary flow. Lack of adequate saliva causes discomfort in denture wearing patients and decreases retention of dentures. The ability of saliva to wet the tissue surface is one of the most important properties for oral comfort and retention of complete denture in dry mouth patients. Aim: This study was conducted to evaluate and compare the wetting ability of therapeutic Aloe vera saliva substitute and commercially available Aqwet saliva substitute on heatpolymerized acrylic resin. Contact angle of liquid saliva substitute was considered as an indicator of wettability. Materials and Methods: Aloe vera liquid (Aloe vera – Group I) and Aqwet saliva substitute (Aqwet – Group II) were compared in terms of their wetting ability. Forty samples of heat-polymerized acrylic resin were fabricated and divided into two groups with 20 samples in each. Advancing, receding contact angles and angle of hysteresis were measured using contact angle goniometer and DSA4 software analysis. Mann-Whitney U test was applied for statistical analysis of the study. Results: The mean advancing angle and receding angle of Group I (Aloe vera) was smaller than Group II (Aqwet). Mean angle of hysteresis of Group I (Aloe vera) was higher than Group II (Aqwet). Mann-Whitney U test revealed that there is no significant difference in contact angles between the two groups. Conclusion: Wetting ability of Group I (Aloe vera) saliva substitute was found to be better compared to Group II (Aqwet) on heat-polymerized acrylic resin.